An in vitro model of tissue boundary formation for dissecting the contribution of different boundary forming mechanisms1. Issue 3 (9th March 2015) - Javaherian, Sahar; D'Arcangelo, Elisa; Slater, Benjamin; Zulueta-Coarasa, Teresa; Fernandez-Gonzalez, Rodrigo; McGuigan, Alison P.
<x xml:space="preserve">Abstract</x> Separation of phenotypically distinct cell populations is necessary to ensure proper organization and function of tissues and organs therefore understanding fundamental mechanisms that drive this cell segregation is important. In this work, authors present an in vivo model system that accurately recapitulates important aspects of cell segregation in vivo and allows dissection of cell behaviours driving cell segregation.